If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + 4) = 12 Reorder the terms: 3(4 + y) = 12 (4 * 3 + y * 3) = 12 (12 + 3y) = 12 Add '-12' to each side of the equation. 12 + -12 + 3y = 12 + -12 Combine like terms: 12 + -12 = 0 0 + 3y = 12 + -12 3y = 12 + -12 Combine like terms: 12 + -12 = 0 3y = 0 Solving 3y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '3'. y = 0 Simplifying y = 0
| 2b-10=5-3b | | 12.5x=10.5 | | -6b=-5b+10 | | 2(y-8)=20 | | 7h=4+6h | | (7(x+5)-18)+(3(x-2)+4)= | | 12.3x-9.2=3x-0.7x | | x+(x*1.08)=188000 | | 7(-3+6x)=-21 | | 2x+3=5x-4+7 | | x^4+1500x^2+1250000=0 | | x*23=33 | | 7x=3x+26 | | 8x-(3x-6)=26 | | 7(2x-1)=11x+5 | | 2a+7=-2-3 | | H=68t-8t | | (9(y+5)-18)+(3(y-3)+5)= | | 5=7-7x | | p^2+4p+4=40 | | 2x-(x+1)= | | (8y-5)6y-7= | | 4(x+5)5=2x-4 | | 6d-11/2=2d-13/2 | | (X+10)2=y+100 | | 24x+19x=180 | | 7/10x=14/5 | | 17-x=172 | | 70-61x+4x^2=0 | | -3=-6-x | | -24+5x+x^2=0 | | x^3+3x^2-15x=0 |